#TITLE_ALTERNATIVE# - ARYA PAMUNGKAS (NIM : 12207053), YULIUS
Prior to developing a gas field, a reservoir study is necessary to conduct to be able to create a development scenario that could generate an optimum gas production. The studies are often conducted by using a reservoir simulator. By doing reservoir simulations we can also predict the field ability to produce gas. A good reservoir model is required in order to observe the reservoir behavior. In the BY-A gas field, the data availability is limited and the reservoir model has not been developed properly. Therefore, it is a necessary to develop the model in advance, before making a production scenario. With these limited data, the model development are done by adjusting the reservoir properties i.e. porosity and permeability. The result of this development is then validated based on geological data exist. The next development stage is to plan production scenarios from a simulation model that has been validated before. Some scenarios is created with several production parameter i.e. well location, the number of wells and gas field production rate. The best development scenario of BY-A Gas Field can be determined by doing analysis for some variables such as cumulative gas production, the plateau time and the recovery factor.